Is the current disposal process of unwanted drugs efficient? Perspectives and roles of Boots - Morissette, Helene (2006)
The disposal of unwanted drugs became an essential service in 2005 following the introduction of the new NHS Community Pharmacy Contractual Framework. The new contract now requires all pharmacy contractors to collect returned medicines from customers. The arrangements to collect them from pharmacies as well as the costs of disposal are taken in charge by the local Primary Care Trusts via waste management contractors. The process therefore involves a wide array of actors. Moreover, the current process is subject to a wide and complex range of waste management legislations resulting in a significant management complexity.